Sustainable Production and Characterization of Biodiesel from Kitchen Waste - Ezemonye Esther Chinaza; Ibe Raymond Obinna; Nnadikwe Johnson; Iheme Chigozie (Journal Majelis Paspama, 2025)
This study demonstrates the sustainable production of biodiesel from waste palm oil through alkaline transesterification, utilizing methanol and sodium hydroxide (NaOH) as catalyst. Under optimal conditions (200 ml methanol and 16 g NaOH per liter of waste oil), an 85% biodiesel yield was achieved. The physicochemical properties of the biodiesel, including density (0.87 g/cm³), viscosity (4.5 mm²/s), flash point (160 °C), cetane number (52), and acid value (0.45 mg KOH/g), meet international standards (ASTM D6751, EN 14214). The results show that waste palm oil is a viable, low-cost, and environmentally friendly feedstock, offering a promising alternative to fossil diesel. The study employed a combination of transesterification, settling, and washing processes to produce high-quality biodiesel. This research contributes to sustainable urban waste management and highlights the potential for biodiesel production from waste oils in developing countries, providing a pathway towards renewable energy and reduced environmental impact.